Inhibition of lanosterol synthase linking with MAPK/JNK signaling pathway suppresses endometrial cancer - Liangjian Ma; Wunan Huang; Xiaolei Liang; Hongli Li; Wei Yu; Lexin Liu; Yuelin Guan; Chang Liu; Xiangjun Chen; Lidan Hu (Cell Death Discovery)
Abstract Endometrial cancer (EC) is a significant health threat to women, with recurrence after treatment posing a major challenge. While abnormal cholesterol metabolism has been implicated in EC progression, the underlying mechanisms remain unclear. In this study, we identified lanosterol synthase (LSS) as a key mediator in cholesterol metabolism associated with EC. We found that LSS is significantly upregulated in EC tissues. Functional assays revealed that LSS promotes cell proliferation and migration, inhibits apoptosis, and drives tumor growth in vivo. Mechanistically, LSS exerts dual effects by accumulating cholesterol esters, thereby enhancing EC cell growth, and activating the MAPK/JNK signaling pathway. Importantly, inhibition of LSS with the specific inhibitor Ro 48-8071 not only reduced EC cell proliferation and suppressed xenograft tumor growth but also inhibited the growth of patient-derived tumor-like cell clusters (PTCs). These findings establish LSS as a novel oncogene in EC, promoting tumor progression through MAPK/JNK signaling activation and cholesterol ester accumulation, and highlight the therapeutic potential of targeting LSS in EC treatment.